Age Differences in Age Perceptions and Developmental Transitions - Chopik, William J.; Bremner, Ryan H.; Johnson, David J.; Giasson, Hannah L. (Frontiers in Psychology, 2018)
Is 50 considered “old”? When do we stop being considered “young”? If individuals could choose to be any age, what would it be? In a sample of 502,548 internet respondents ranging in age from 10 to 89, we examined age differences in aging perceptions (e.g., how old do you feel?) and estimates of the timing of developmental transitions (e.g., when does someone become an older adult?). We found that older adults reported older perceptions of aging (e.g., choosing to be older, feeling older, being perceived as older), but that these perceptions were increasingly younger than their current age. The age to which individuals hope to live dramatically increased after age 40. We also found that older adults placed the age at which developmental transitions occurred later in the life course. This latter effect was stronger for transitions involving middle-age and older adulthood compared to transitions involving young adulthood. The current study constitutes the largest study to date of age differences in age perceptions and developmental timing estimates and yielded novel insights into how the aging process may affect judgments about the self and others.